2005
DOI: 10.1016/j.cell.2004.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the Plasma Membrane Na+/Ca2+ Exchanger in Excitotoxicity

Abstract: In brain ischemia, gating of postsynaptic glutamate receptors and other membrane channels triggers intracellular Ca2+ overload and cell death. In excitotoxic settings, the initial Ca2+ influx through glutamate receptors is followed by a second uncontrolled Ca2+ increase that leads to neuronal demise. Here we report that the major plasma membrane Ca2+ extruding system, the Na+/Ca2+ exchanger (NCX), is cleaved during brain ischemia and in neurons undergoing excitotoxicity. Inhibition of Ca2+-activated proteases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
389
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(412 citation statements)
references
References 51 publications
17
389
5
1
Order By: Relevance
“…It is characterized by a dramatic increase in [Ca 2 þ ] i following the activation of Ca 2 þ -permeable receptors, particularly glutamate receptors, even after the stimulus has ended, thought to be due to loss of the mitochondrial ability to buffer intracellular Ca 2 þ . [28][29][30][31] More recently, it was demonstrated that, in cerebellar granule neurons, NCX also participates in this process of secondary Ca 2 þ overload, 14 due to its loss of the ability to pump Ca 2 þ out of the cell, following its proteolytic inactivation by calpains upon exposure to glutamate, providing a new hypothesis for the origin of delayed Ca 2 þ deregulation. Hoyt et al 32 have shown in cultured rat forebrain neurons that, although reversal of NCX contributes to Ca 2 þ transients and to the immediate rise in intracellular Ca 2 þ levels upon exposure to glutamate, it has no effect in the mean peak increase caused by a prolonged exposure to glutamate nor does it contribute to neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by a dramatic increase in [Ca 2 þ ] i following the activation of Ca 2 þ -permeable receptors, particularly glutamate receptors, even after the stimulus has ended, thought to be due to loss of the mitochondrial ability to buffer intracellular Ca 2 þ . [28][29][30][31] More recently, it was demonstrated that, in cerebellar granule neurons, NCX also participates in this process of secondary Ca 2 þ overload, 14 due to its loss of the ability to pump Ca 2 þ out of the cell, following its proteolytic inactivation by calpains upon exposure to glutamate, providing a new hypothesis for the origin of delayed Ca 2 þ deregulation. Hoyt et al 32 have shown in cultured rat forebrain neurons that, although reversal of NCX contributes to Ca 2 þ transients and to the immediate rise in intracellular Ca 2 þ levels upon exposure to glutamate, it has no effect in the mean peak increase caused by a prolonged exposure to glutamate nor does it contribute to neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, the involvement of calpains in the cleavage of NCX was described in cultured cerebellar granule neurons exposed to glutamate and following brain ischemia. 14 The NCX3 subtype is inactivated by proteolytic cleavage by calpains, and is no longer able to pump Ca 2 þ out of the cell, thus enhancing cell death. Furthermore, NCX3 was shown to be more relevant for cell survival than NCX1 or NCX2, namely in cultured cerebellar granule neurons.…”
mentioning
confidence: 99%
“…ENaC, T-type Ca 2+ channels) and ion exchange systems (Na + /H + , Na + /Ca 2+ exchanger). Recent studies have suggested that the normal activity of Na + /Ca 2+ exchanger, for example, is critical for maintaining cellular Ca 2+ homeostasis and the survival of neurons against delayed calcium deregulation and injury caused by glutamate receptor activation [53]. Conversely, inhibition of Na + /Ca 2+ exchanger by amiloride is expected to compromise normal neuronal Ca 2+ handling, which may transform the Ca 2+ transient elicited by non-toxic glutamate concentrations into a lethal Ca 2+ overload.…”
Section: Pharmacological Characterization Of Asics Amiloridementioning
confidence: 99%
“…66 Along the same lines, the Na þ /Ca 2 þ transporter type 1 is also cleaved by caspase-3 in cerebellar granule neurons undergoing apoptosis. 68 Two final aspects require attention. Firstly, the idea that a [Ca 2 þ ] er decrease protects cells from the effect of apoptotic agents may appear in contrast with the established notion that treatment of cells with SERCA inhibitors (thapsigargin, tBuBHQ, and cyclopiazonic acid) is followed by apoptosis.…”
Section: The Correlation Of the Calcium-signalling Alteration With Sementioning
confidence: 99%